Pengaruh Kurs dan Pertumbuhan Ekonomi terhadap Return Saham pada Sektor Keuangan Bursa Efek Indonesia - Sugiyanto Ikhsan (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2022)
Exchange rate is an important aspect in economic growth in Indonesia, because it will affect the workings of the national economy, especially stock returns, the results of previous studies show different results related to exchange rates with stock returns, while economic growth on stock returns is very consistent. This study aims to examine the effect of the exchange rate on stock prices in the financial sector, and examine the effect of economic growth on stock prices as an effort to confirm the results of previous studies. This study uses a quantitative approach with an empirical method, the data used begins in the 2009-2018 period, a time series model with a Vector Autoregressive (VAR) approach where if the data used is statistic and not co-integrated. The VAR model shows that in simultaneous equations, if there are simultaneous relationships between observed variables, then these variables must be treated equally, so that there are no more endogenous and exogenous variables. The results show that the exchange rate and economic growth has no effect on stock returns. Macroeconomic aspects namely the exchange rate and economic growth in the period 2009-2018 shows that there is no influence on stock returns of the financial sector which are listed on the Indonesia Stock Exchange.